Collaborative Classrooms: Promoting Science Students' Collaboration Through STEM Learning Integration in the Era of Educational Resilience - Nurramadhani, Annisa; Riandi, Riandi; Permanasari, Anna; Suwarma, Irma Rahma (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
STEM learning has increasingly been implemented in higher education, particularly in science education programs. In the aftermath of the global health crisis, the learning process has transitioned to a new normal, significantly different from pre-crisis practices. Numerous changes and challenges have emerged in science learning, particularly in fostering collaboration among prospective teachers in higher education. This research explores the nature of collaboration among prospective science teachers through the integration of STEM learning, employing a qualitative research method with in-depth observation as the primary data collection technique. Observations were conducted directly and supported by video recordings to ensure comprehensive data collection, with collaborative practices assessed using collaborative learning rubrics. The findings reveal that science education students have improved their collaboration skills through STEM learning integration, showing greater comfort in direct discussions and hands-on investigative learning activities, although some topics still require online discussions facilitated by e-learning platforms. Consequently, a blended learning approach is identified as the most effective method for integrating STEM learning in the current era to enhance collaboration in science education. Future research could further investigate the integration of STEM learning using hybrid learning models to promote collaboration among students.